Synthesis of graphene oxide membranes on polyester substrate by spray coating for gas separation. (23rd November 2018) - Ibrahim, Amr F.M.; Lin, Y.S.
Graphical abstract: Highlights: High quality GO membranes can be coated on polymer substrate by spray coating method. Prepared GO membranes offer gas characteristics similar to those made by filtration. Dilute GO suspension in spray coating reduces the formation of extrinsic wrinkles. Less wrinkles results in reduction in the porosity of inter-layer galleries. Less wrinkles leads to higher selectivity of H2 over large gas molecules. Abstract: Graphene oxide (GO) membranes have shown promising gas separation characteristics specially for hydrogen showing potential for industrial applications. However, GO membranes made by filtration, the most common synthesis method, contain wrinkles affecting their gas separation characteristics and the method itself is difficult to scale up. In this work, high quality GO membranes are made from GO suspension by easily scalable spray coating technique (and also by filtration method for comparison) on hydrophilic polyester track etch substrates. GO sheet suspensions of large sheet average size (33 µm) and dilute concentrations are used to minimize GO sheet edge-to-edge interactions and minimize extrinsic wrinkle formation. Single gas permeation and separation experiments of equimolar H2 /CO2 binary mixture were conducted to evaluate the permeation and separation characteristics of prepared membranes. GO membranes prepared by spray coating offer gas characteristics similar to those made by filtration, however using dilute GO suspension in spray coating reduces the formation of extrinsic wrinkles causing reduction in the porosity of the inter-sheet pathway where the transport of large gas molecules dominates. This study demonstrates an efficient, scalable and cost-effective approach for synthesizing large area GO membranes with enhanced hydrogen separation.